Advances in endovascular treatment of acute ischaemic stroke. Issue 8 (August 2015) - Asadi, H.; Dowling, R.; Yan, B.; Wong, S.; Mitchell, P.
Abstract Over the past decade, there have been rapid advancements in ischaemic stroke reperfusion treatments. However, clear clinical benefit is yet to be shown in large clinical trials. In this review, the major studies in different types of endovascular treatments including intra‐arterial thrombolysis, aspiration devices, mechanical clot retrievers and the new stent retrievers are discussed. First‐generation mechanical thrombectomy devices such as the MERCI Retriever (Stryker, Kalamazoo, MI, USA) and Penumbra aspiration device (Penumbra Inc., Alameda, CA, USA) demonstrated safety and higher rates of recanalisation in the MERCI and Penumbra Pivotal Stroke Trial; however, there was no significant improvement in clinical outcome. Second‐generation endovascular stent retrieval devices Solitaire (ev3 Neurovascular, Irvine, CA, USA) and Trevo (Stryker) have shown promising results. In preliminary trials, SOLITAIRE with the Intention for Thrombectomy (SWIFT) and Thrombectomy Revascularization of Large Vessel Occlusions (TREVO), both showed rates of recanalisation close to 90% and significantly improved clinical outcomes compared with the MERCI study, but the recent landmark studies for endovascular treatment (Interventional Management of Stroke (IMS III), Mechanical Retrieval and Recanalisation of Stroke Clots Using Embolectomy (MR‐RESCUE) and SYNTHESIS) did not show any clinical benefit from endovascular treatment compared with standard intravenous therapy. However, moving forward, the recent Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischaemic Stroke in the Netherlands (MR‐CLEAN) study results have shown marked improvements in recanalisation, reperfusion and functional outcome in patients receiving endovascular treatment (97% using stent retrievers) within 6 h in addition to standard medical care. Overall, although evidence regarding the efficacy of endovascular treatment in acute stroke has been equivocal, recent publications of large multicentre randomised controlled trials indicate benefit of intra‐arterial stent retriever reperfusion in patients selected by appropriate imaging and treated early by experienced operators, and it will likely remain an important adjunct to established medical treatment with intravenous tPA.